2019
DOI: 10.29252/jrdms.4.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ardox-X Active Oxygen-Containing Toothpaste on Periodontal Parameters in Dentate and Implant-Wearing Patients

Abstract: ARTICLE INFO Article HistoryBackground and Aim: Reducing the number of pathogenic microorganisms can contribute to reducing the incidence and epidemiology of periodontal diseases. This study aimed to evaluate the clinical effects of Ardox-X active oxygen-containing toothpaste on periodontal indices in patients with at least 1 to 2 implants. Materials and Methods:In this crossover randomized clinical trial, 30 subjects were randomly divided into two groups (n=15). Oral hygiene instructions were delivered to all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…(31) Piattelli et al used Bio-Oss in sinus augmentation procedures and found small capillaries, mesenchymal cells, and osteoblasts inside some Haversian canals in the specimens harvested at 6 months with no inflammation present. (32,33) Bae et al clinically evaluated the use of Osteon as a sinus bone grafting material. (11) They concluded that bone healing is not greatly affected if the perforation site is reconstructed using appropriate techniques.…”
Section: Discussionmentioning
confidence: 99%
“…(31) Piattelli et al used Bio-Oss in sinus augmentation procedures and found small capillaries, mesenchymal cells, and osteoblasts inside some Haversian canals in the specimens harvested at 6 months with no inflammation present. (32,33) Bae et al clinically evaluated the use of Osteon as a sinus bone grafting material. (11) They concluded that bone healing is not greatly affected if the perforation site is reconstructed using appropriate techniques.…”
Section: Discussionmentioning
confidence: 99%